Pengaruh Kompetensi Terhadap Kinerja Karyawan PT. Pelabuhan Indonesia IV (Persero) Cabang Merauke - Putri Inggrid Maria Risamasu (Musamus Journal of Business & Management is a peer-reviewed journal published by Faculty of Ecconomics and Business, Musamus University, Merauke Papua Indonesia., 2019)
This study aims to determine how much competency affects the performance of employees at PT Pelabuhan Indonesia IV (Persero) Branch Merauke. The population in this study, as many as 32 respondents with a total sampling technique in which 32 respondents were made as samples. This study uses a quantitative approach with simple linear regression analysis techniques. The procedure for collecting data uses interview methods and questionnaires, and the data is processed using SPSS version 20. The results of the study show that competence has a positive and significant effect on the performance at PT Pelabuhan Indonesia IV (Persero) Branch Merauke , indicated by the X regression coefficient of 0.751.